Synthesis, crystal structure, and nonlinear optical behavior of beta-unsubstituted meso-meso E-vinylene-linked porphyrin dimers. - Frampton, M; Akdas, H; Cowley, A; Rogers, J; Slagle, J; Fleitz, P; Drobizhev, M; Rebane, A; Anderson, H (2005)
[structure: see text] A vinylene-linked porphyrin dimer, with no substituents at the beta-positions, has been synthesized by CuI/CsF promoted Stille coupling. In the crystal structure of this dimer, the C(2)H(2) bridge is twisted by 45 degrees relative to the plane of the porphyrins. The absorption, emission spectra, and electrochemistry reveal substantial porphyrin-porphyrin pi-conjugation. The triplet excited-state absorption spectrum of this dimer makes it suitable for reverse saturable absorption at 710-900 nm.